Plasma Sprayed Bioceramic Coatings on Ti-Based Substrates: Methods for Investigation of Their Crystallographic Structures and Mechanical Properties - Iordanova, Ivanka; Antonov, Vladislav; Sprecher, Christoph M.; Skulev, Hristo K.; Gueorguiev, Boyko (IntechOpen, 2012)
None